Improving drinking water safety in recreational parks through policy changes and regulatory support in the Hunter New England region, NSW, Australia. Issue 4 (2nd October 2019) - Jaravani, Fidelis G.; Durrheim, David N.; Judd, Jenni; Oelgemöller, Michael; Butler, Michelle; Massey, Peter D.
ABSTRACT: Recreational parks in the Hunter New England region of New South Wales, Australia, are very popular. Ensuring drinking water safety in the parks requires the application of a considered risk management approach. The study evaluated the compliance of public recreational parks with the NSW Public Health Act 2010 and NSW Public Health Regulation 2012 requirements to implement Quality Assurance Programs. Between March and August 2016, drinking water supplies in 54 national and three state recreational sites in regional Hunter New England were surveyed to evaluate whether the recommendations from the initial survey of 2010–2011 were implemented . The results were compared to the first survey results. All recreational sites developed and implemented drinking water quality assurance programs, compared to four during the first survey. Fifty two of 57 (91%) sites had warning signs at water outlets compared to 34 (60%) during the first survey. There were statistically significant improvements in the provision of water quality warning signs and implementation of water quality assurance programs ( p  < 0.0001 McNemar Chi 2 Test) between the first and second surveys demonstrating a good example of beneficial policy change, with regulatory support. Further research is required to understand the ongoing challenges of drinking water management in recreational parks.